Germination and performance of seven native wildflowers in the Mediterranean landscape plantings - Scarici, Enrico; Ruggeri, Roberto; Provenzano, Maria Elena; Rossini, Francesco (Italian Journal of Agronomy, 2017)
The use of native species in landscape design is a choice related to environmental sustainability and it contributes to the aesthetic appeal of urban and marginal areas. However, to date, the lack of knowledge of the ecological characteristics and agronomic practices of these species, represents a limit for their use. This study aims to obtain information about germination ecology, morphological traits and ornamental value of 7 selected perennial native taxa, with potential use in meadows seed mixtures for the Mediterranean environment. Seed germination for each taxon was assessed under different conditions (temperature, photoperiod and pre-treatment) in a controlled environment, while data on plant performances was collected from field plots. In general, the dormant seeds showed a positive response to pre-treatment with gibberellic acid (GA3) and chilling within a period of about six months from the time of seed collection. The dependence of germination on light and temperature was observed in most of the tested taxa. Differences in plant height and flowering dynamics gave practical directions in terms of combining seeds of different species to create and maintain a wildflower meadow in low-maintenance areas. Crepis bursifolia L. and Hypochaeris radicata L. were the only two species, which showed good persistence during the two-year field study and met the aesthetic requirements of low-input Mediterranean landscaping. Our study by adding original findings to the limited knowledge available on wildflower sowing in the Mediterranean environment, contributes to the development of sustainable strategies in the greening projects designed for those peculiar climatic conditions.